Конструктивно-географічні підходи до організації міського середовища - Гілета, Л. А. (Київський національний університет імені Тараса Шевченка, 2016)
Розглянуто міське середовище, яке характеризується поєднанням геосистем різного походження (антропогенних, антропогенно-модифікованих і природних). Проаналізовано генеральний план міста, який створюють органи місцевого самоврядування для організації міських систем. Визначено, що містобудівна діяльність не враховує конструктивно-географічних підходів до організації міського середовища, що призводить до ущільнення міської забудови та виникнення ряду екологічних проблем.

We examined the urban environment, which performs a lot of functions and is characterized by a combination of geosystems of different genesis (anthropogenic, modified anthropogenic and natural ones). This combination produces the need to organize the urban environment, a process which is carried out by local governments that develop a general plan of a city. But we determined that city planning does not include structural and geographic approaches to the organization of the urban environment. Nevertheless, the organization of urban environment entails streamlining of this environment and aims to create the city that is the most favorable one for the life of its residents. Using Lviv as an example, we characterized the general plan of the city that anticipates an increase in population and, respectively, in housing. This results in crowded city buildings and emergence of many environmental problems, in particular air pollution due to the increasing number of vehicles and the use of independent heating. The increase in population also requires expanding the capacity of sewage treatment facilities, increasing the number of green spaces and solving the problem of garbage. Modern development of urban systems should be based on the structural and geographical approaches to their organization, which includes a series of studies, including the physical and geographical conditions of the urban environment; the permissible settlement load on a whole urban ecosystem or on its individual parts (districts); the impact of the existing industrial facilities on the environment and on the health of city dwellers; as well as studying the negative impact of the existing and the projected transport systems and analysis of green spaces of the city as areas that weaken the negative factors of the urban environment and the possibility of their expansion. Otherwise, city planning will lead to a number of environmental problems.
Structural and geographical approaches to the organization of the urban environment
Keywords: міське середовище; організація містобудівної діяльності; генеральний план міста; urban environment; organization of city planning; city General Plan